A Review on Low Power SRAM - Patil, Manasi (Journal of Advanced Research in Applied Artificial Intelligence and Neural Network; Vol 3 No 2 (2019): Journal of Advanced Research in Applied Artificial Intelligence and Neural Network, 2021)
In any digital system, memory is main part and no digital system can be completed without memories. Now a days Embedded system and compact size devices are developed.  So low power consumption is an important issue in system design. In VLSI design, the main issues are increased packing density, scaling in silicon technology and optimizing the speed. Due to these, there is increased power dissipation in system. So, there is a need to design a low power SRAM to increase run time with small size and high performance. In this paper basic operation of SRAM and different techniques to reduce total power dissipation are discussed. How to cite this article: Patil M. A Review on Low Power SRAM. J Adv Res Appl Arti Intel Neural Netw 2019; 2(2): 9-12.